Severe chemical eye injuries - clinical outcomes and associated socio-economic factors - Borja Salvador-Culla; Jeffrey Hogg; Arthur Okonkwo; Julie Mulroy; Gustavo S. Figueiredo; Francisco C. Figueiredo (SAGE Publishing, 2023)
Aims To describe clinical outcomes, management, and socio-economic impact of severe acute chemical eye injuries in a tertiary hospital. Methods 37 patients required emergency admission to the Royal Victoria Infirmary eye ward between April 2013 and September 2015. Demographics, best corrected distance visual acuity (BCDVA), causative agent, degree of limbal stem cell deficiency (LSCD), management and socio-economic data were evaluated. Results Mean age on admission was 34.5 years (SD 16.3; range 16-82); 30 males (81.1%); 22 bilateral (59.5%). Causative agent: alkali in 30 cases (81.1%); acid in three cases (8.1%); and unknown in four cases (10.8%). Fifteen cases (40.5%) were assaults, 12 (32.5%) work-related accidents, nine (24.3%) domestic accidents and one (2.7%) undetermined. Eleven patients (29.7%) were unemployed, 18 (48.6%) were labourers, three (8.1%) were students, three (8.1%) were retired and two (5.4%) were professionals. Mean admission time was five days (SD 3.2; range 1-12). Mean follow-up time was 170.5 days (range 1-946). Mean cost of admission was £2478 (range £274-5785). Five patients (13%; seven eyes) developed total or partial limbal stem cell deficiency, all being assaults. Conclusions Main causative agent in our study was alkali, with young men in the working age being most frequently involved. Many patients required prolonged hospital admission and costly follow-up. The majority of cases were assaults, mostly occurring in unemployed patients. All the limbal stem cell deficiency cases were due to assaults. We believe that socio-economic factors play an important role in the cause, severity and cost of chemical eye injuries. Lay Summary Acute chemical eye injuries have a significant and extensive impact on patients' visual function outcomes and vision-related quality of life, with consequent enormous burden to affected individuals, their families and society. We believe that by understanding the socio-economic environment, we may not only be able to enforce safety measures to tackle the increasing rate of severe chemical eye injuries in our community, but also to develop collaborative programmes with the community, educating the population on the seriousness of chemical eye injuries, and with the local authorities, trying to understand the clustering of assaults in areas and tackling the associated socio-economic risk factors, such as unemployment. Given the increasing rate of assaults using chemicals in recent times, it is also important to assess availability of adequate victim support programmes and develop good interaction with relevant local, regional and national authorities to ensure all aspects of community security service are in place to be able to address any potential deficiencies in line with police and home office guidelines. Keeping in mind that the best action plan is always prevention. However, when an ocular injury does occur it is evident that significant morbidity and visual sequelae can result and affect the socio-economic status of the victims despite our best current medical and surgical care.